HOTEL FRANCHISING IN RUSSIA IN THE LIGHT OF THE DOMESTIC TOURISM DEVELOPMENT - M. S. Shakhova (Модернизация, инновация, развитие)
This article discusses future prospects of franchising development of hotel chains in Russia. The relevance is due to the strong growth of domestic tourism in recent years. So, it becomes necessary to increase the number of hotels and rise the quality of tourist services.Goal/objectives. The purpose of this article is to identify the advantages of franchising for the development of hotel chains. To achieve this goal, the author has posed and solved the following tasks: analyze the current situation on the hotel market of Russia, tendencies of its development, uncovered potential hotel franchise for the successful development of domestic tourism in Russia.Methodology. The theoretical basis of this article leans on the work of Russian researchers, in the hotel industry, analyst reports made by consulting companies. Also the author takes into account experience of real participants of this business. As a methodological basis of this article, the author used: analysis, synthesis, analogy, comparison, induction and deduction.Results. Franchising is one of the most eff ective ways of of hotel business development today, which, unfortunately, has not yet received wide distribution in Russia.Conclusions/significance. The development of domestic tourism in every country requires a stable growth in the amount of hotels and an improvement of tourism services quality.Current world practice proves that hotel franchising could help to reach this target. In spite of novelty of franchising in Russian industry, this tool has already successfully used in major international hotel chains in several Russian regions. And today Russian hotel chains more and more approve the benefits of franchising development. However, the its development is slow due to the unfavorable business climate in Russia.